Molecular and Insilico Characterization of Antimicrobial Resistant Escherichia fergusonii and Morganella morganii causing Urinary Tract Infections: Antimicrobial Resistant Bacteria causing UTI - Muhammad Haris,; Rizwan Abbas,; Sidra Rahman,; Muhammad Waseem, (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2024)
Urinary tract infections (UTIs) are a major public health concern causing mortality and morbidity worldwide. There are approximately 13,000 deaths that are linked to UTIs every year. Bacterial antibiotic resistance is increasing globally, making it difficult to treat urinary tract infections. Biochemical tests have resulted in inaccurate identification, due to which wrong empirical treatment of antibiotics is prescribed. The present research work aims to identify rare bacterial isolates along with the assessment of antibiotic resistance patterns. A total of 339 samples were examined for urine cultures. Based on biochemical testing, three positive samples were selected. Culture sensitivity results revealed two multidrug-resistant and one extensively drug-resistant bacteria. MDR strains showed sensitivity to meropenem, gentamicin, cefoperazone-sulbactam, nitrofurantoin, tigecycline and imipenem, and co-amoxiclav while XDR bacteria showed sensitivity to nitrofurantoin and tigecycline. The 16S rRNA sequencing results revealed two Escherichia fergusonii strains and one Morganella morganii strain. Our findings revealed the identification of rare and opportunistic bacteria less reported from Pakistan. In addition, it is the first report of E. fergusonii from Pakistan. In conclusion, using molecular identification of rare and neglected bacteria via PCR is more sensitive and highly specific than other identification methods. In the future, this approach will help in accurate diagnosis and will help in minimizing antibiotic resistance.